A revision of Parapterogramma Papp and Pseudopterogramma Papp, with a review of the Parapterogramma genus group of the Pacific and Indomalayan regions (Diptera, Sphaeroceridae, Limosininae) - Gregory K. Kuwahara; Stephen A. Marshall; Stephen P.L. Luk (European Journal of Taxonomy)
The “Pterogramma-like” genera of the Pacific and Indomalayan regions (Archipterogrammoides Papp, 2008, Minialula Papp, 2008, Parapterogramma Papp, 2008, Pseudopterogramma Papp, 2008, Pterogrammoides Papp, 2008) are reviewed and treated as a monophyletic group of three genera, here referred to as the Parapterogramma genus group. The following 13 new Parapterogramma and three new Pseudopterogramma species are described: Pa. bicolor sp. nov. (Fiji), Pa. dentatum sp. nov. (Papua New Guinea), Pa. digitisternum sp. nov. (Australia), Pa. gonitellum sp. nov. (Australia), Pa. hieroglyphicum sp. nov. (Fiji, New Caledonia), Pa. magnum sp. nov. (Australia), Pa. matau sp. nov. (Fiji), Pa. ofiensis sp. nov. (Papua New Guinea), Pa. peckorum sp. nov. (Fiji), Pa. pollex sp. nov. (Fiji), Pa. pugioformis sp. nov. (Australia, Papua New Guinea), Pa. simplex sp. nov. (Fiji), Pa. tokotaai sp. nov. (Fiji), Ps. fijiensis sp. nov. (Fiji), Ps. kasut sp. nov. (Indonesia, Singapore), and Ps. ketambensis sp. nov. (Indonesia, Malaysia). Archipterogrammoides is treated as a new junior synonym of Pseudopterogramma, resulting in the following new combinations: Pseudopterogramma aestivale (Richards, 1973) comb. nov., Pseudopterogramma deemingi (Richards, 1973) comb. nov., and Pseudopterogramma metatarsalis (Papp, 2008) comb. nov. Minialula is treated as a new junior synonym of Parapterogramma, resulting in the following new combinations: Parapterogramma poeciloptera (Papp, 2008) comb. nov., Parapterogramma continentalis (Hayashi, 2013) comb. nov., and Parapterogramma tropicalis (Hayashi, 2013) comb. nov. A key to the species of the Parapterogramma genus group is provided.